Design and Simulation of Synchronous Buck Converter in Comparison with Regular Buck Converter - Hossein Zomorodi; Erfan Nazari (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
In a variety of low-power applications, a step-down dc-dc converter is used to reduce the voltage from a higher level. The two types of dc-dc converters are a regular buck and synchronous buck. The synchronous buck utilizes two switches and one diode, whereas the regular buck uses one switch and one diode. Many converters rely on the power components' switching qualities to work. A second MOSFET is required due to the diode's higher conduction losses. Because of the diode's conduction losses, the converter's efficiency may be reduced. The use of a synchronous buck converter improves efficiency by reducing diode losses. The main goal of this study is to compare and contrast these two low-power step-down converters. The simulation in this work was performed using the LTSPICE program.